Biology and genomics of an historic therapeutic Escherichia coli bacteriophage collection - Baig, Abiyad; Colom, Joan; Barrow, Paul; Schouler, Catherine; Moodley, Arshnee; Lavigne, Rob; Atterbury, Robert J. (Frontiers, 2017)
We have performed microbiological and genomic characterization of an historic collection of nine bacteriophages, specifically infecting a K1 E. coli O18:K1:H7 ColV+ strain. These phages were isolated from sewage and tested for their efficacy in vivo for the treatment of systemic E. coli infection in a mouse infection model by Smith and Huggins (1982). The aim of the study was to identify common microbiological and genomic characteristics, which co-relate to the performance of these phages in in vivo study. These features will allow an informed selection of phages for use as therapeutic agents. Transmission electron microscopy showed that six of the nine phages were Podoviridae and the remaining three were Siphoviridae. The four best performing phages in vivo belonged to the Podoviridae family. In vitro, these phages exhibited very short latent and rise periods in our study. In agreement with their microbiological profiles, characterization by genome sequencing showed that all six podoviruses belong to the Autographivirinae subfamily. Of these, four were isolates of the same species (99% identity), whereas two had divergent genomes compared to other podoviruses. The Siphoviridae phages, which were moderate to poor performers in vivo, exhibited longer latent and rise periods in vitro. Two of the three siphoviruses were closely related to each other (99% identity), but all can be associated with the Guernseyvirinae subfamily. Genome sequence comparison of both types of phages showed that a gene encoding for DNA-dependent RNA polymerase was only present in phages with faster replication cycle, which may account for their better performance in vivo. These data define a combination of microbiological, genomic and in vivo characteristics which allow a more rational evaluation of the original in vivo data and pave the way for the selection of phages for future phage therapy trails.